Optimization of Coffee Plantation Waste into Certified Cascara Based on a Circular Economy - Ade Anggun Wana Putri; Abdul Jabbar; Amnan Haris (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2026)
Peron Village, Kendal Regency, is one of the coffee production centers in Central Java that generates large amounts of coffee husk waste. This waste has the potential to cause environmental problems if it is not properly managed. Coffee husks can be processed into cascara, a value-added product that supports the concept of a circular economy. This article aims to describe efforts to optimize coffee plantation waste into certified cascara products through assistance in fulfilling food safety standards and business legal requirements. This activity is part of the Student Organization Capacity Building Program (PPK Ormawa) implemented in Peron Village, involving the Sekar Group as a partner. The implementation method employed a participatory approach through several stages, including problem identification using Participatory Rural Appraisal (PRA), assistance in the cascara production process, socialization on the importance of SP-PIRT certification, technical and administrative assistance, sanitation counseling, as well as monitoring and evaluation. The indicators of success for this activity included active member participation, administrative readiness, successful processing of coffee husk waste, a more hygienic and standardized production process, increased understanding of food safety, and the issuance of an SP-PIRT certificate (one document). The results show an increase in the partners’ capacity for the hygienic and sustainable processing of coffee husk waste, improved understanding of food regulations, and enhanced business administrative readiness. This assistance successfully facilitated the issuance of an SP-PIRT certificate for the cascara product “Peronara Tea,” which has contributed to increased consumer confidence and expanded product marketing opportunities. Thus, the optimization of coffee husk waste based on a circular economy approach, supported by business legality, has proven to strengthen the competitiveness and sustainability of community-based MSMEs.